Preventing Terrorism Threats: Implementation and Challenges in the Indo-nesia’s New Capital City - Wardana, Irfanditya Wisnu; Arfina, Zora; Priyanto , Sapto (LEGAL BRIEF, 2025)
: The relocation of Indonesia’s capital to Nusantara presents security challenges, particularly in preventing terrorism. Existing counterterrorism frameworks lack integration between urban planning, technological security, and community-based strategies. This study examines the role of AI-based surveillance, biometric security, and cybersecurity alongside participatory approaches to enhance resilience and detect radicalization early. Key issues include gaps in policy coordination, the effectiveness of digital surveillance, and the role of local communities in countering extremist narrative. A qualitative content analysis identifies patterns and challenges in terrorism prevention. Findings highlight the need for synergy among the government, society, and technology. Practical recommendations include an integrated security framework combining smart surveillance, adaptive policies, and cross-sector collaboration. With a comprehensive approach, Nusantara can serve as a model for a secure and resilient capital city